Preconceito contra nordestino: uma espécie de racismo tipificado? - Ferreira, Davi Rocha (2016)
This research aims on the study of discriminatory offenses against the northeastern, with the focus of its criminalization as a specific modality of the crime of racism, investigating if these behaviors are typified and respect the constitutional postulate of legality. The importance of the subject is due to the fact that people are responding to lawsuits for an offense imprescriptible and unsafable. In addition, the investigation was carried out through the reading of Brazilian criminal legal literature, the analysis of debates in the Chamber of Deputies about the legislative evolution of the norms that criminalize racism and through the comparison of STF leading cases. Finally, the study allowed to conclude that the discriminatory offense against northeastern people is not typified in art. 20 of the racism law (Law 7.716/1989).